2019
DOI: 10.1186/s12967-019-2077-y
|View full text |Cite
|
Sign up to set email alerts
|

The protective role of microRNA-21 against coxsackievirus B3 infection through targeting the MAP2K3/P38 MAPK signaling pathway

Abstract: Background The P38 mitogen-activated protein kinase (MAPK) pathway plays an essential role in CVB3-induced diseases. We previously demonstrated microRNA-21 has potential inhibitory effect on the MAP2K3 which locates upstream of P38 MAPK and was upregulated in mouse hearts upon CVB3 infection. However, the effect and underlying mechanism of miRNA-21 on CVB3 infection remain unclear. Methods We detected continuous changes of cellular m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 41 publications
2
31
0
Order By: Relevance
“…Additionally, MiR-98 decreased cell apoptosis by targeting the FAS/FASL gene (Zhang B. Y. et al, 2016 ), and miR-21 reduced cell apoptosis by targeting programmed cell death 4 (PDCD4) (He et al, 2013 ), a well-known apoptosis gene (Gaur et al, 2011 ; Stagakis et al, 2011 ; Junker et al, 2015 ). Furthermore, another study confirmed that miR-21 reduced cell apoptosis by targeting mitogen-activated protein kinase kinase 3 (MAP2K3) (He et al, 2019 ). Interestingly, although both studies showed that miR-21 has an anti-apoptosis effect, the expression trend of miR-21 was not consistent after CVB3 infection in different studies ( Table 2 ).…”
Section: The Role Of Mirnas In Cvb3-induced Vmcmentioning
confidence: 90%
“…Additionally, MiR-98 decreased cell apoptosis by targeting the FAS/FASL gene (Zhang B. Y. et al, 2016 ), and miR-21 reduced cell apoptosis by targeting programmed cell death 4 (PDCD4) (He et al, 2013 ), a well-known apoptosis gene (Gaur et al, 2011 ; Stagakis et al, 2011 ; Junker et al, 2015 ). Furthermore, another study confirmed that miR-21 reduced cell apoptosis by targeting mitogen-activated protein kinase kinase 3 (MAP2K3) (He et al, 2019 ). Interestingly, although both studies showed that miR-21 has an anti-apoptosis effect, the expression trend of miR-21 was not consistent after CVB3 infection in different studies ( Table 2 ).…”
Section: The Role Of Mirnas In Cvb3-induced Vmcmentioning
confidence: 90%
“…For instance, miR-21 could act as a protective factor during Coxsackievirus B3 (CVB3) infection, by targeting the MAP2K3/p38 MAPK pathway. In this process, miR-21 has been shown to inhibit the expression of MAP2K3, leading to a reduced phosphorylation of the p38 MAPK, thus resulting in a significant decrease in the release of viral progeny (Figure 3; He et al, 2019). Also acting upon the same pathway are miR-744, miR-24 and miR-124, which are considered potential antiviral agents for RSV virus and influenza.…”
Section: Mapk Signaling Pathwaymentioning
confidence: 99%
“…In this case, the miRNAs involved are miR-24, miR-124, and miR-744. However, besides the decrease in the activation of p38 component due to a lack of phosphorylation, there has also been demonstrated a reduction in the overall levels of the same member (McCaskill et al, 2017;He et al, 2019).…”
Section: Figure 3 | (A)mentioning
confidence: 99%
“…MiR-21 was found to play a protective role also against coxsackievirus B3 (CVB3) infection-induced heart infection, likely via targeting the MAP2K3/p-38 MAPK signaling pathway. In a mouse model of CVB3 infection, miR-21 pretreatment inactivated MAP2K3/p-38 MAPK signaling and exerted cardioprotection manifested by alleviated cell apoptosis and reduced necrosis in the heart, accompanied by reduced viral titers and the remarkably prolonged survival time of animals [172]. The overall picture of the cardioprotective action of miR-21 is outlined in Figure 4.…”
Section: Role Of Mir-1 and Mir-21 In Cardioprotection Other Than Ischmentioning
confidence: 99%
“…isoflurane-induced up-regulation of miR-21 associated with ↓PDCD4 protected cardiomyocytes against H 2 O 2 injury [166] isoflurane protected mouse hearts exposed to I/R via miR-21 and Akt/NOS/mPTP [167] trimetazidine-induced ↑miR-21 accompanied by cardioprotection against I/R, ↑p-Akt and ↑Bcl-2/Bax in rats. Cardioprotection reversed by anti-miR-21 [169] miR-21 enhanced protective effect of loperamide against H/R injury in rat cardiomyocytes associated with ↓ROS and ↓apoptosis [170] Non-pharmacological miR-1 down-regulation of miR-1 by traditional Chinese medicine Tanshinone IIA led to cardioprotection via inhibition of I/R-induced p-38 MAPK in rats [173] phenolic compound paeonol exerts cardioprotection against epirubicin-induced heart injury via regulation of miR-1, PI3K/AKT/mTOR and NF-κB [176] miR-21 resveratrol-induced up-regulation of miR-21 associated with protection against I/R in rats [168] miR transfection and delivery miR-21 adenovirus miR-21 transfection decreased IS via targeting PDCD4/AP-1 [62] adenovirus miR-21 transfection improved LV remodeling & ↓apoptosis in cardiac I/R in rats [67] lentivirus miR-21 transfection induced cardioprotection against I/R in mice manifested by ↓IS, ↓fibrosis and ↓apoptosis [64] miR-21 transfection to human cardiomyocytes ↓apoptosis via JNK/p38-MAPK/caspase-3 [68] chemically synthesized exogenous miR-21 reduced IS in mice, miR-21-induced protection was abolished with miR-21 inhibitor co-treatment [165] nanoparticle delivery of miR-21 to cardiac macrophages post-MI promoted angiogenesis, reduced hypertrophy, fibrosis, and apoptosis in the remote myocardium [75] miR-21 pretreatment exerted cardioprotection against CVB3 infection via targeting MAP2K3/p38-MAPK in mice [172] Exosomal miR miR-21 depletion of exosomal miR-21 reduced protective effect of conditioned medium in H 2 O 2 -induced oxidative stress in cardiomyocytes, and in rat hearts exposed to AMI [69] ↑miR-21 in CPC-derived exosomes prevented apoptosis in H9c2 cells via ↓PDCD4 [70] Abbreviations: I/R: ischemia/reperfusion; H/R: hypoxia/reoxygenation; AMI/MI: (acute) myocardial infarction; PDCD4: programmed cell death protein 4; AP-1: activator protein 1 (downstream molecule of PDCD4); ROS: reactive oxygen species; IS: infarct size; LV: left ventricle; CPC: cardiac progenitor cell; AF: atrial fibrillation; IPC: ischemic preconditioning; IPostC: ischemic postconditioning; RIPC: remote ischemic preconditioning; RIPerC: remote ischemic preconditioning; CVB3: coxsackievirus B3.…”
Section: Type Of Intervention Mir Findings Referencementioning
confidence: 99%